A Protocol For Developing A Machine Learning Model To Forecast Healthcare Treatment Resource Utilization - Mohd Noor Afiq Ramlee; Mohd Hafiz Jaafar; Mohd Iqbal Mohd Noor; Amirah Azzeri; Adzly Hairee; Amira Mas Ayu Amir Mustafa (Malaysian Journal of Public Health Medicine (MJPHM), 2024)
Indexed by Scopus